Electrode Wear Rate of Graphite Electrodes during Electrical Discharge Machining Processes on Titanium Alloy Ti-5Al-2.5Sn - Khan, Md. Ashikur Rahman; M. M., Rahman; K., Kadirgama (Universiti Malaysia Pahang, 2014)
The proper selection of machining parameters can result in better machining performance in the electrical discharge machining process. However, this job is not always easy since the phenomena occurring between the electrodes in EDM are not yet fully understood. This study reports the development of a comprehensive mathematical model for the electrode wear rate (EWR) of a graphite tool in EDM on Ti-5Al-2.5Sn alloy, which has not yet been presented. Experiments for positive polarity of the graphite electrode, based on design of experiment (DOE), are first conducted. Modeling and analysis are carried out through the response surface methodology, utilizing the experimental results. A confirmation test is also executed to confirm the validity and the accuracy of the mathematical model developed. The confirmation test exhibits an average error of less than 6%. Negative electrode wear is evidenced for particular settings. The combination of 15A peak current, 350µs pulse-on time, 180µs pulse-off time and 95V servo-voltage and positive polarity causes negative tool wear. It is apparent that the developed model can evaluate electrode wear rate accurately and successfully.